2019
DOI: 10.1186/s12876-019-1019-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quality of segmental bowel preparation on adenoma detection rate

Abstract: Background The effectiveness in surveillance colonoscopy largely depends on the quality of bowel preparation. We aimed to investigate the quality of bowel preparation segmentally and its effect on Adenoma Detection Rate (ADR) and Advanced Adenoma Detection Rate (AADR) at corresponding bowel segments. Methods This is a single-centered and cross-sectional study. A consecutive of 5798 patients who underwent colonoscopy examination were included. Bowel preparation was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Our results support a recent cross-sectional study that showed an increased ADR with BBPS 3 versus 2 in over 4900 patients [25]. Our results are compatible with high-quality studies concluding lack of ADR improvement with higher-than-adequate bowel cleansing [6,26].…”
Section: Discussionsupporting
confidence: 91%
“…Our results support a recent cross-sectional study that showed an increased ADR with BBPS 3 versus 2 in over 4900 patients [25]. Our results are compatible with high-quality studies concluding lack of ADR improvement with higher-than-adequate bowel cleansing [6,26].…”
Section: Discussionsupporting
confidence: 91%
“…[ 22 ] Several previous studies have reported an association between BBPS and adenoma detection rate. [ 23 , 24 ] The adenoma detection rate of the colonoscopist serves as the quality indicator for a screening colonoscopy. Some studies have reported no relationship between endoscopist fatigue and adenoma detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evaluation of intestinal preparation quality should be more comprehensive and include the evaluation of bowel air bubbles. Guo et al used the bubble score as a supplement to the BBPS score to evaluate intestinal cleanliness in order to explore the detection rate of colorectal adenoma (43). They found that 65.7% of patients had bowel air bubbles that affected visual field observation, and the bowel air bubbles were negatively correlated with the detection rate of adenoma.…”
Section: Discussionmentioning
confidence: 99%